Diagnosis and Treatment of Obesity: A TBL Exercise for Third-Year Medical Students - Lisa Strano-Paul; Susan Lane (Association of American Medical Colleges, 2015)
Abstract Obesity is a multifactorial chronic disease associated with numerous common medical problems. Obese patients are at increased risk of mortality. Successful recognition and treatment of obesity should be a goal for all primary care providers. This 1-hour team-based learning (TBL) module is designed to teach third-year medical students how to screen for obesity and define it based on National Heart, Blood, and Lung Institute criteria. Students explain which diseases are associated with obesity and devise a treatment plan for obese patients. This TBL session provides third-year students with an active learning format for the evaluation and treatment of obesity. Students have indicated in written and verbal feedback that this module is highly effective in achieving its objectives when taught during an ambulatory medicine rotation.